Modeling diameter distributions in Önsen natural stone pine (Pinus pinea L.) stands - Fatih Si̇vri̇kaya; Ramazan Karakaş (Turkish Journal of Forestry, 2020)
In this study, parameters of Weibull function with three parameters were predicted for natural Stone Pine stands in Önsen town, which is in Kahramanmaraş Regional Directorate of Forestry Kahramanmaraş Directorate of State Forest Enterprise, Hartlap Forest Enterprise Chief. To model diameter distribution of natural Stone Pine, 30 sample plots were taken from field survey and six different methods were used for predicting parameters of Weibull function with three parameters. Error index values were applied for comparison of different parameter estimation methods. Percentile-Based method, which use 25%, 50% and 95% of diameter values together and have 2.967 average rank number, is the greatest successful function to define diameter distributions for Stone Pine based on error index values estimated by differences between actual diameter distribution and predicted diameter distribution in accordance with different parameter estimation methods.
Keywords: hibrit; diameter distribution; hybrid; olasılık yoğunluk fonksiyonu; probability density function; weibull dağılımı; Forestry; SD1-669.5; çap dağılımı; weibull distribution; 15. Life on land